Expression of Insulin-Like Growth Factor System Genes During the Early Postnatal Neurogenesis in the Mouse Hippocampus - Zhang, Jihui (2007)
Insulin-like growth factor-1 (IGF-1) is essential to hippocampal neurogenesis and the neuronal response to hypoxia/ischemia injury. IGF (IGF-1 and -2) signaling is mediated primarily by the type 1 IGF receptor (IGF-1R) and modulated by six high-affinity binding proteins (IGFBP) and the type 2 IGF receptor (IGF-2R), collectively termed IGF system proteins. Defining the precise cells that express each is essential to understanding their roles. With the exception of IGFBP-1, we found that mouse hippocampus expresses mRNA for each of these proteins during the first 2 weeks of postnatal life. Compared to postnatal day 14 (P14), mRNA abundance at P5 was higher for IGF-1, IGFBP-2, -3, and -5 (by 71%, 108%, 100%, and 98%, respectively), lower for IGF-2, IGF-2R, and IGFBP-6 (by 65%, 78%, and 44%, respectively), and unchanged for IGF-1R and IGFBP-4. Using laser capture microdissection (LCM), we found that granule neurons and pyramidal neurons exhibited identical patterns of expression of IGF-1, IGF-1R, IGF-2R, IGFBP-2, and -4, but did not express other IGF system genes. We then compared IGF system expression in mature granule neurons and their progenitors. Progenitors exhibited higher mRNA levels of IGF-1 and IGF-1R (by 130% and 86%, respectively), lower levels of IGF-2R (by 72%), and similar levels of IGFBP-4. Our data support a role for IGF in hippocampal neurogenesis and provide evidence that IGF actions are regulated within a defined in vivo milieu.